Chronic obstructive pulmonary disease and the risk for myocardial infarction by type in people with HIV. (1st April 2023) - Crothers, Kristina; Nance, Robin M.; Whitney, Bridget M.; Harding, Barbara N.; Heckbert, Susan R.; Budoff, Matthew J.; Mathews, William C.; Bamford, Laura; Cachay, Edward R.; Eron, Joseph J.; Napravnik, Sonia; Moore, Richard D.; et al.
Abstract : Objectives: The relationship between chronic obstructive pulmonary disease (COPD) and cardiovascular disease in people with HIV (PWH) is incompletely understood. We determined whether COPD is associated with risk of myocardial infarction (MI) among PWH, and if this differs for type 1 (T1MI) and type 2 (T2MI). Design: We utilized data from five sites in the Centers for AIDS Research Network of Integrated Clinical Systems (CNICS) cohort, a multisite observational study. Methods: Our primary outcome was an adjudicated MI, classified as T1MI or T2MI. We defined COPD based on a validated algorithm requiring COPD diagnosis codes and at least 90-day continuous supply of inhalers. We conducted time-to-event analyses to first MI and used multivariable Cox proportional hazards models to measure associations between COPD and MI. Results: Among 12 046 PWH, 945 had COPD. Overall, 309 PWH had an MI: 58% had T1MI ( N = 178) and 42% T2MI ( N = 131). In adjusted models, COPD was associated with a significantly increased risk of all MI [adjusted hazard ratio (aHR) 2.68 (95% confidence interval (CI) 1.99–3.60)] even after including self-reported smoking [aHR 2.40 (95% CI 1.76–3.26)]. COPD was also associated with significantly increased risk of T1MI and T2MI individually, and with sepsis and non-sepsis causes of T2MI. Associations were generally minimally changed adjusting for substance use. Conclusion: COPD is associated with a substantially increased risk for MI, including both T1MI and T2MI, among PWH. Given the association with both T1MI and T2MI, diverse mechanistic pathways are involved. Future strategies to decrease risk of T1MI and T2MI in PWH who have COPD are needed.